Combined CNV, haplotyping and whole exome sequencing enable identification of two distinct novel EYS mutations causing RP in a single inbred tribe. Issue 12 (4th December 2018) - Wormser, Ohad; Gradstein, Libe; Kadar, Einat; Yogev, Yuval; Perez, Yonatan; Mashkit, Elena; Elbedour, Khalil; Drabkin, Max; Markus, Barak; Kadir, Rotem; Halperin, Daniel; Khalaila, Soltan; et al.
Abstract: Whole exome sequencing (WES) has become routine in clinical practice, especially in studies of recessive hereditary diseases in inbred consanguineous families, where homozygosity of a founder mutation is assumed. Multiple members of two consanguineous families of a single Bedouin tribe were diagnosed with apparently autosomal recessive/pseudo‐dominant retinitis pigmentosa (RP). Affected individuals exhibited severe visual impairment with nyctalopia, marked constriction of visual fields, markedly reduced and delayed responses on electro‐retinography (ERG) and eventual loss of central vision. Combined copy‐number variant (CNV) analysis, haplotype reconstruction and WES of the kindred identified two distinct novel mutations in EYS (RP25): a p.(W1817*) nonsense mutation (identified through WES) and a large deletion encompassing 9 of the 43 exons, that was missed by WES and was identified through microarray CNV analysis. Segregation analysis of both mutations demonstrated that all affected individuals were either homozygous for one of the mutations, or compound heterozygous for both. The two mutations are predicted to cause loss of function of the encoded protein and were not present in screening of 200 ethnically‐matched controls. Our findings of two distinct mutations in the same gene in a single inbred kindred, identified only through combined WES and microarray CNV analysis, highlight the limitations of either CNV or WES alone, as the heterozygous deletion had normal WES read‐depth values. Moreover, they demonstrate pitfalls in homozygosity mapping for disease‐causing variant identification in inbred communities.